2015
DOI: 10.1155/2015/902821
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Comparison of QUANTA Flash dsDNA Chemiluminescent Immunoassay with Four Current Assays for the Detection of Anti-dsDNA Autoantibodies

Abstract: Introduction. The objective of the present study was to compare QUANTA Flash dsDNA, a chemiluminescent immunoassay (CIA) on the BIO-FLASH, a rapid-response chemiluminescent analyzer, to three other anti-dsDNA antibody assays and to Crithidia luciliae indirect immunofluorescence test (CLIFT). Methods. In the first part of the study, 161 samples, 61 from patients suffering from systemic lupus erythematosus (SLE) and 100 from a disease control group, were tested by QUANTA Flash dsDNA CIA, QUANTA Lite dsDNA SC ELI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 21 publications
2
30
0
4
Order By: Relevance
“…In terms of clinical performance, the sensitivity in SLE (54.3%) and specificity (89.8%) in the disease controls is similar to previous studies on the CIA and other anti-dsDNA solid phase assays; however, it is important to note that in general there is a high degree of variability reported among the studies for both sensitivity and specificity of the anti-dsDNA methods evaluated. [8][9][10]13,18 In particular, Infantino et al 18 reported a 96.0% specificity (95% CI 90.1-98.9%) and 39.3% sensitivity (95% CI 27.2-52.7%) for the CIA in an Italian cohort, while this study demonstrated lower . Whether the patients have active or inactive disease; .…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…In terms of clinical performance, the sensitivity in SLE (54.3%) and specificity (89.8%) in the disease controls is similar to previous studies on the CIA and other anti-dsDNA solid phase assays; however, it is important to note that in general there is a high degree of variability reported among the studies for both sensitivity and specificity of the anti-dsDNA methods evaluated. [8][9][10]13,18 In particular, Infantino et al 18 reported a 96.0% specificity (95% CI 90.1-98.9%) and 39.3% sensitivity (95% CI 27.2-52.7%) for the CIA in an Italian cohort, while this study demonstrated lower . Whether the patients have active or inactive disease; .…”
Section: Discussionmentioning
confidence: 83%
“…The majority of studies comparing different anti-dsDNA antibody assays focused on the ability to discriminate between SLE and controls. 8,10,13,18,27 Only a few studies have analyzed the tests for their performance to measure disease activity in SLE patients. [4][5][6][7]15 Our data demonstrated that the novel CIA shows a good correlation to the disease activity measured by the SLEDAI-2K score.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the current availability of novel antigenic preparations (recombinant, highly purified extracts, circular plasmids and synthetic oligonucleotides), along with other methodological improvements, has led to the production of new generation immunoassays that are able to detect anti-dsDNA only of intermediate and high avidity [49]. Consequently, the detection of anti-dsDNA autoantibodies for the diagnosis of SLE can be reliably executed by adopting the latest immunoassay techniques, which includes CLIA methods, and reports a quantitative result [50, 51]. …”
Section: Changing Operation Protocolsmentioning
confidence: 99%